Effects of floriculture enterprise on the well-being of young floriculturists in Ibadan metropolis, Oyo state, Nigeria (2017)
Effects of floriculture enterprises on the wellbeing of youth in Ibadan metropolis was investigated. Three Local Government Areas were purposively selected, and random sampling was employed to select 30% of the registered floriculturists from the list of 388 members to give a total of 117 respondents. A structured questionnaire was used to collect data and analysed using descriptive and inferential statistics. Findings reveal 56.4% had a favourable attitude towards floricultural enterprise, while 70.1% had a high level of well-being. Age, marital status and attitude towards floriculture were significantly influenced the wellbeing status of the respondents. The study, therefore, recommended intensification of youth empowerment programmes in floriculture enterprise in the study area.